2020
DOI: 10.1007/s11606-020-05971-3
|View full text |Cite
|
Sign up to set email alerts
|

Association Between State-Level Income Inequality and COVID-19 Cases and Mortality in the USA

Abstract: Figure 1 The unadjusted correlation between the state-level Gini index and the number of COVID-19 cases (a) and deaths (b).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
106
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(136 citation statements)
references
References 2 publications
15
106
1
1
Order By: Relevance
“…To our knowledge, this is the first study to show that cross-national differences in COVID-19 mortality relate to income inequality. This finding aligns with studies that found associations between inequality and various measures of population health ( Pickett and Wilkinson, 2015 ; Ram, 2006 ) and recent evidence from the United States ( Mollalo et al, 2020 ; Oronce et al, 2020 ). The association held up to multiple controls, including country wealth and social capital, and therefore is not well explained by differences in trust, as suggested elsewhere ( Pickett and Wilkinson, 2015 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…To our knowledge, this is the first study to show that cross-national differences in COVID-19 mortality relate to income inequality. This finding aligns with studies that found associations between inequality and various measures of population health ( Pickett and Wilkinson, 2015 ; Ram, 2006 ) and recent evidence from the United States ( Mollalo et al, 2020 ; Oronce et al, 2020 ). The association held up to multiple controls, including country wealth and social capital, and therefore is not well explained by differences in trust, as suggested elsewhere ( Pickett and Wilkinson, 2015 ).…”
Section: Discussionsupporting
confidence: 91%
“…New research (e.g., Ahmed et al, 2020 ; Takian et al, 2020 ) has observed a similar pattern in COVID-19, with more transmission and worse health outcomes in poorer populations due to overcrowded housing and work conditions. Some research in the US recently found moderate correlations between state-level income inequality and COVID-19 cases and deaths ( Mollalo et al, 2020 ; Oronce et al, 2020 ) and other communicable disease (e.g., sexually transmitted disease, tuberculosis; Holtgrave and Crosby, 2003 , 2004 ), however cross-national evidence of a contextual association with COVID-19 is scarce.…”
Section: Introductionmentioning
confidence: 99%
“…As the pandemic has progressed in the US, it has become clear that, the impact of COVID-19 has been felt more acutely in some communities,[ 8 , 9 ] most clearly among Black Americans, who acquire the disease and die at disproportionate rates. [ [10] , [11] , [12] ] Social determinants of health may drive some of this disparity, and neighborhood traits may be particularly relevant, given that infectious disease spread is often influenced by the built environment.…”
Section: Introductionmentioning
confidence: 99%
“…For example, age structure explained part of the between-country differences in COVID-19 mortality and case-fatality rates [4,20]; median prevalence of the five conditions most frequently associated with severe COVID-19 in USA allowed to identify the areas at highest risk for COVID-19 death [21]; age-specific prevalence of comorbidities explained the differences in mortality between Nigeria, Brazil and Italy [22]. Economic and healthcare associated variables are other aggregated data potentially useful to predict COVID-19 severity and spread [68][69][70], as well as inequalities within the general population [71]. Unlike these studies, however, the present analysis considered the mortality rate from an infectious disease that was not somewhat causally associated with COVID-19 mortality and death and was based on a different assumption, namely, that the two diseases shared a set of determinants, ranging from the characteristics of the population at highest risk, to transmission routes, from case and death misclassifications, to the efficiency of the healthcare systems.…”
Section: Determinantmentioning
confidence: 99%